Perceptions of critical success factors in the management of dilapidated schools’ reconstruction projects using Industrialised Building System method in rural areas in Sarawak - Mohammad Shamsudin, Nor Azlin (2021)
The study features the perceptions of critical success factors (CSFs) in managing reconstruction projects. It aims at recognising the CSFs of dilapidated schools’ reconstruction projects in the rural areas in Sarawak, Malaysia. The CSFs for the reconstruction of dilapidated schools differ from building a new school facility because of both are distinctive in project nature. Hence, the objective of this study is to identify the CSFs in the management of a reconstruction dilapidated school projects using the Industrialised Building System (IBS) method. For the reconstruction of dilapidated schools in the rural areas of Sarawak, the Malaysian Government has utilised the Industrialised Building System (IBS) as one of the methods to enhance the efficiency of construction process. Within the broadened studies on IBS, there are evidence that this method is highly preferred in developed countries and in building of residential properties and new structures, but limited studies are found for developing countries and no study has tapped into the work of reconstruction of an existing building. Although the IBS method is expected to shorten the length of these dilapidated schools’ reconstruction projects, several reconstructions still fail to complete on time as reported by the National Audit Report and vastly in mass media. Therefore, this study seeks to recognise the CSFs that contribute to the management of dilapidated schools’ reconstruction projects through the lens of the tripartite parties involved in the projects i.e. the prime movers, builders and the stakeholders. In analysing the different tripartite perspectives, the study applies the interconnected view of four theories i.e. Complexity Management Theory, Learning Curve Theory, Organisational Theory and Agency Theory. It is important to assimilate elements from the several theories for there is no single theory that could explain the unmitigated and complex process in managing the dilapidated schools’ reconstruction projects. The study adopts the qualitative research method using case studies as the main methodology as it concentrated on the study of twenty dilapidated schools in Sarawak. This methodology is also being reinforced by phenomenological approach as a secondary support to explain the phenomena of the twenty dilapidated schools from the lived experiences of the participants. Semi structured face-to-face interview was conducted in order to achieve the targeted objectives. Ultimately, the findings identify ten significant CSFs which are; sturdy key decision, team commitment, effective communication, competent project team, setting project target, experience of the project manager, good working collaboration, project coordination, close project monitoring and meticulous project planning. This study enhances the existing project management body of knowledge by suggesting corrective actions that when implemented appropriately may prevent project failure. On the other hand, the study also brings great benefit to the project management organisation as it suggests new and improved strategic human resource planning policy for the Government to consider in positioning the right people for the right job in running project management. Finally, it hopes to present new insights towards having a more efficient project management that focuses on rapid execution and high impact initiatives in a strategic and organised working environment.